ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI STRES PERSALINAN - Zulfita Zulfita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Labor is a natural physiological process, yet it frequently causes high levels of anxiety and stress in childbearing women. Unmanaged labor stress can trigger physical and psychological complications for both the mother and the fetus. This study aims to analyze various factors influencing maternal stress levels during the labor process. The primary factors examined include age, parity, education level, spousal support, healthcare provider support, financial anxiety, and history of pregnancy complications. Analysis results indicate that psychological readiness, parity, and emotional social support play a significant role in reducing the threshold of labor stress. A comprehensive understanding of these factors is crucial for midwives and healthcare professionals to design holistic midwifery care interventions that ensure a safe and comfortable childbirth experience. Keywords: Labor Stress, Parity, Social Support, Midwifery